Assessment of Radionuclide Concentration in Surface Soil and Human Health Risk Associated with Exposure in Two Higher Institutions of Esan land, Edo State, Nigeria - F.A. Popoola; O.D. Fakeye; Q.B. Basiru; D.A. Adesina; M.A. Sulola (Journal of Applied Sciences and Environmental Management)
The aim of this study is to assess the activity concentration of radionuclides and the possible health risk associated with exposure to radiation from the soil samples collected from two higher institutions in Esan land of Edo State, Nigeria. The gamma spectrometry system was used to determine the activity concentrations of radionuclides 238U, 232Th and 40K in the surface soil samples. The activity concentration of radionuclides ranged from 7.16 ± 0.63 to 102.37 ± 2.37 BqKg-1for 40K, from 0.75 ± 0.05 to 3.13 ± 0.11 BqKg-1 for 238U and from 2.25 ± 0.20 to 9.02 ± 0.40 BqKg-1for 232Th. The measured mean activity concentration of radionuclides for 40K, 238U and 232Th from the examined topsoil of Samuel Adegboyega University were 57.80 ± 1.7 BqKg-1; 2.07 ± 0.09 BqKg-1 and 6.89 ± 0.34 BqKg-1 respectively. At the neighbouring higher institution; College of Education, Igueben, the mean activity concentration of 40K, 238U and 232Th in its surface soil were 30.19 ± 1.22 BqKg-1, 1.41 ± 0.07 BqKg-1 and 4.85 ± 0.28 BqKg-1 respectively. The total mean values for radiation dose estimation for Radium Equivalent Activity, Absorbed Dose, Excess Lifetime Cancer Risk, Outdoor and Indoor Annual Effective Dose Equivalent are 13.20 BqKg-1, 6.03 nGy/ℎ, 0.026, 7.40 µSτ/γ and 29.60 µSτ/γ respectively. These values were found to be lower than the global average values. Hence, there is no radiation induced health threat to the students and members of staff in the study area.